A Comprehensive Review on Natural Bioactive Compounds and Probiotics as Potential Therapeutics in Food Allergy Treatment - Pratap, Kunal; Taki, Aya C.; Johnston, Elecia B.; Lopata, Andreas L.; Kamath, Sandip D. (Frontiers in Immunology, 2020)
Food allergy is rising at an alarming rate and is a major public health concern. Globally, food allergy affects over 500 million people, often starting in early childhood and increasingly reported in adults. Commercially, only one approved oral immunotherapy-based treatment is currently available and other allergen-based immunotherapeutic are being investigated in clinical studies. As an alternative approach, a substantial amount of research has been conducted on natural compounds and probiotics, focusing on the immune modes of action, and therapeutic uses of such sources to tackle various immune-related diseases. Food allergy is primarily mediated by IgE antibodies and the suppression of allergic symptoms seems to be mostly modulated through a reduction of allergen-specific IgE antibodies, upregulation of blocking IgG, and downregulation of effector cell activation (e.g. mast cells) or expression of T-helper 2 (Th-2) cytokines. A wide variety of investigations conducted in small animal models or cell-based systems have reported on the efficacy of natural bioactive compounds and probiotics as potential anti-allergic therapeutics. However, very few lead compounds, unlike anti-cancer and anti-microbial applications, have been selected for clinical trials in the treatment of food allergies. Natural products or probiotic-based approaches appear to reduce the symptoms and/or target specific pathways independent of the implicated food allergen. This broad range therapeutic approach essentially provides a major advantage as several different types of food allergens can be targeted with one approach and potentially associated with a lower cost of development. This review provides a brief overview of the immune mechanisms underlying food allergy and allergen-specific immunotherapy, followed by a comprehensive collection of current studies conducted to investigate the therapeutic applications of natural compounds and probiotics, including discussions of their mode of action and immunological aspects of their disease-modifying capabilities.